Significance of SME Loans on the CMSME Entrepreneurs’ Socio-economic Development and Financial Performance: Bangladesh Perspective - Roy, Gourav; Akter, Mahmuda; Ghosh, Anidra (Dhaka University Journal of Business Studies, 2026)
The SME sector contributes nearly 25% of the GDP of Bangladesh and 80% of workforce of Bangladesh is engaged to SME sectors. The study employs a mixed-method methodology to identify whether SME loans can significantly impact the socioeconomic development of entrepreneurs. Again, the study investigates which categories of loanees of Cottage, Micro, Small, Medium and Large (CMSME) entrepreneurs can absorb the advantages of SME loans. Finally, the study determines whether SME loans have impacted the financial performance of the SME loan recipients. Because there are five clusters, including cottage, micro, small, medium, and large enterprises, the study specifically encountered each of them with the same questionnaire, collected a primary data set in Likert scale from 467 CMSME enterprises throughout Bangladesh, and statistically tested the responses. As a result of the ordinal responses being configured, the reliability and validity of the questionnaire were tested with Cronbach’s Alpha. Using Linear Probability Model Regression with Variance Covariance Estimator (VCE) and Ordered Logit Regression with Variance Covariance Estimator (VCE), the study found significance in the first objective. The study found that cottage, micro, and small enterprises mostly benefited, respectively, from this loan. Using the log normalized values of net income before and after the loans received by these entrepreneurs, the study employed a paired t-test and confirmed that there is a significant impact of SME loans on the financial performance of the SME loan recipients. The novelty of this research lies in its comprehensive inclusion of all CMSME clusters within a single empirical framework. The study contributes to the existing field of literature by linking the firm performance and socio-economic development. Journal of Business Studies, Vol. XLIV, No. 1, 2025 Page 107-137